2004
DOI: 10.1212/01.wnl.0000094199.60829.f5
|View full text |Cite
|
Sign up to set email alerts
|

Low androgenization index in elderly women and elderly men with Alzheimer’s disease

Abstract: The authors investigated whether testosterone levels and testosterone availability differ between older lean subjects with and without Alzheimer's disease (AD). Sex hormone binding globulin (SHBG) and estradiol levels were higher, whereas the free androgenization index (FAI) was lower, in lean subjects with AD than in lean subjects without AD. Factors involved in the increase of SHBG secretion could have an important role in the lower testosterone availability of subjects with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 10 publications
4
69
0
Order By: Relevance
“…In subsequent studies by this group, both total (Hogervorst et al, 2004;Hogervorst et al, 2003;Lehmann et al, 2004) and free (Hogervorst et al, 2002) testosterone levels were found to be significantly lower in men without AD irrespective of potentially confounding such indices as age, education, body mass index, smoking, alcohol use, diabetes, and hormone therapy. Similar findings of low testosterone in men with AD have been reported in several (Almeida et al, 2004;Moffat et al, 2004;Paoletti et al, 2004;Rasmuson et al, 2002;Watanabe et al, 2004) but not all (Pennanen et al, 2004) studies. Interestingly, low testosterone has also been linked to several other neurodegenerative diseases, including Parkinson's disease (Okun et al, 2004), vascular dementia (Watanabe et al, 2004), amyotropic lateral sclerosis (Militello et al, 2002), and Huntington's disease (Markianos et al, 2005).…”
Section: Age-related Androgen Depletion and Alzheimer's Diseasesupporting
confidence: 88%
“…In subsequent studies by this group, both total (Hogervorst et al, 2004;Hogervorst et al, 2003;Lehmann et al, 2004) and free (Hogervorst et al, 2002) testosterone levels were found to be significantly lower in men without AD irrespective of potentially confounding such indices as age, education, body mass index, smoking, alcohol use, diabetes, and hormone therapy. Similar findings of low testosterone in men with AD have been reported in several (Almeida et al, 2004;Moffat et al, 2004;Paoletti et al, 2004;Rasmuson et al, 2002;Watanabe et al, 2004) but not all (Pennanen et al, 2004) studies. Interestingly, low testosterone has also been linked to several other neurodegenerative diseases, including Parkinson's disease (Okun et al, 2004), vascular dementia (Watanabe et al, 2004), amyotropic lateral sclerosis (Militello et al, 2002), and Huntington's disease (Markianos et al, 2005).…”
Section: Age-related Androgen Depletion and Alzheimer's Diseasesupporting
confidence: 88%
“…Prior work from several research groups including our own has linked both AD (Hogervorst et al 2001(Hogervorst et al , 2003Moffat et al 2004;Paoletti et al 2004;Rosario et al 2004) and elevated Ab levels (Gandy et al 2001; Gillett et al Fig. 7 DHT-induced decrease in Ab levels is dependent on an ARmediated pathway.…”
Section: Discussionmentioning
confidence: 85%
“…The observation that estradiol levels control brain SHBG expression [24] also suggests that SHBG is involved in neuroendocrine control. Serum SHBG levels have been shown to increase in patients with Alzheimer’s disease [25, 26]. Further studies need to be done to demonstrate whether changes in central SHBG exist in various neurodegenerative ailments.…”
Section: Discussionmentioning
confidence: 99%